Homo and heterologous expression of the HpPKS2 gene in Hypericum perforatum and Bacopa monnieri - Khan, Shamshad Ahmad; Verma, Priyanka; Parasharami, Varsha A. (Plant Cell Tissue and Organ Culture, 2022)
Hypericum perforatum has been known to produce hypericin and hyperforin that are used in treating mild to moderate depression. The HpPKS2 (H. perforatum polyketide synthase 2) gene is assumed to play a role in hypericin biosynthesis. The HpPKS2 gene was overexpressed in homologous H. perforatum in vitro grown plants through Agrobacterium tumefaciens-mediated genetic transformations. It leads to the establishment of seven glass house acclimatized transgenic lines. Among them, the HP12 transgenic plant showed 9.8 fold enhancement in hypericin content (379.4 +/- 10.3 mu g/g dry wt) followed by 3-fold in HP41 (117.1 +/- 4.5 mu g/g dry wt) as compared to control plants. This was further supported by the real-time PCR studies where it registered up to 5 fold enhancement of HpPKS2 gene expression. On the other hand, the heterologous expression of the HpPKS2 gene in Bacopa monnieri resulted in the establishment of five transgenic plant clones that were successfully acclimatized under glasshouse conditions. Among them, BT4 was found to be very slow-growing. The BT3 line showed maximum expression of the HpPKS2 gene which surprisingly also upregulates the expression of the other metabolic pathway genes of B. monierri namely isopentyl- diphosphate delta isomerase (IDDI), squaline synthase (SQS) and acetyl CoA C acetyltransferase (AA). The HPLC analysis in the heterologous system revealed the maximum production of bacopaside I (9.86 +/- 1.0 mg/g dry wt), bacopaside II (5.89 +/- 0.9 mg/g dry wt) and bacopasaponin C (3.59 +/- 0.3 mg/g dry wt) by transgenic lines BT8, BT3 and BT4, respectively. This enhancement in bacopaside I, bacopaside II and bacopasaponin C production was more than 26-fold, 5-fold and 21-fold, respectively in comparison to the control non transformed plants. Key message Overexpression of the HpPKS2 gene in H. perforatum led to higher hypericin content in the native system while its expression in the heterologous system i.e. B. monnieri also improves bacopaside I, bacopaside II and bacopasaponin C production.
Keywords: Agrobacterium tumefacience; Bacopa monnieri; Bacopasides; Heterologous expression; HpPKS2; Hypericin; Hypericum perforatum; Transgenics